Identification Project
For the purposes of processing the records of the PHR, two of their Bosnia projects, the Antemortem Database Project (AMDB) and the Identification Project (IP) have been combined as one sub-fond description, the Identification Project. The many similarities and intersections between the two projects necessitate this merger. The AMDB project involved the collecting of Antemortem (before death) information on persons registered as missing by the ICRC (Red Cross). This information, describing the person in detail, was obtained as the result of interviews conducted with relatives of the missing persons. All this information was put unto the special computer database designed for this purpose. The Identification Project (IP) involved matching this antemortem data with evidence obtained from mass graves exhumed around Bosnia with the help of the PHR. Identifications were made by matching clothes and personal effects found with the bodies to descriptions given by the relatives of the missing. But the most important and decisive element of the IP involved DNA matching between samples taken from the bodies, and blood samples taken from maternal relatives. There are five series within this IP sub-fond: Identified Cases giving the details of individuals successfully identified by the project, Lists of Missing Persons drawn up by the PHR and the ICRC listing the missing by municipality, Tracing Requests forms by which families applied for an investigation of their missing relatives, Interviews and Questionnaires detailing the work of the AMDB, and Medical Records covering DNA testing and post-mortems (autopsies). Accruals not expected